PERTANGGUNGJAWABAN HUKUM PEMERINTAH (Kajian Tentang Ruang Lingkup Dan Hubungan Dengan Diskresi) - Julista Mustamu (Faculty of Law, Universitas Pattimura, 2014)
The concept of government responsibility in this paper gives the sense of an obligation for theauthorities to take responsibility for legal use of power that can cause harm to citizens. Theconcept of responsibility is meant here is responsibility in the legal sense is really related totheir rights and obligations. This paper will examine the issue of government responsibility inthe administration of state freely associated with the government's authority in theadministrative law concept known as discretionary.